The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.18848/1447-9516/cgp/v07i04/36841
|View full text |Cite
|
Sign up to set email alerts
|

A Small Scale Study into the Effect that Text & Background Colour has on Processing and Self-Correction Rates for Childrens’ On-Screen Reading

Abstract: Pedagogical practices in formal educational settings together with the nature of communication technologies in the media and elsewhere mean that children will encounter on-screen typography and screen-based learning opportunities in both formal school settings and during their daily recreational pursuits. Internationally, there is a lack of research informing what good reading practice might look like when teachers use reading material in a screen-based environment. More specifically, there is a lack of resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…Another recurring sentiment from the students interviewed found a strong preference for traditional black text on white as a colour combination, however, this combination was used infrequently in the observed lessons. This is similar to the findings of Vanderschantz et al (2010) who found that their second largest group of respondents considered Black on White text to be their preferred reading condition, while the largest group of respondents in that study had no preference. In that same study it was found that 58 of 61 students claimed that Black on White was the most common colour combination that they read, this may explain this preference.…”
Section: Recommendationssupporting
confidence: 88%
See 1 more Smart Citation
“…Another recurring sentiment from the students interviewed found a strong preference for traditional black text on white as a colour combination, however, this combination was used infrequently in the observed lessons. This is similar to the findings of Vanderschantz et al (2010) who found that their second largest group of respondents considered Black on White text to be their preferred reading condition, while the largest group of respondents in that study had no preference. In that same study it was found that 58 of 61 students claimed that Black on White was the most common colour combination that they read, this may explain this preference.…”
Section: Recommendationssupporting
confidence: 88%
“…Sufficient contrast between text and background colours was present in the majority of the flipcharts, however in a selection of slides, contrast lacked completely. This contradicts the advice of Vanderschantz et al (2010) who showed that children's self correction and error rates for reading on screen, can be negatively affected by poor contrast and colour.…”
Section: Typographic Colourmentioning
confidence: 64%
“…The majority of recent research relating to colour in interface design is related to preference and aesthetics, (cites), our study therefore reinforces the need for further investigation into the effective use of colour in interface design, especially when it forms a key part of the usability of the interface. Vanderschantz et al, (2010) identify that readers have both emotional and physical responses to colour and the use of colour can be motivational both in print and on screen.…”
Section: Addressing Observed Issuesmentioning
confidence: 99%
“…Colour is of particular interest in typographic presentation as indicated by Vanderschantz et al (2010) who discussed evidence that color combinations in children's on-screen reading material can affect children's' ability to comprehend text. This is supported by research conducted with text in print and with adults (Bix, 2002;Fukuzumi, Yamazaki, Kamijo, & Hayashi, 1998;Hill & Scharff, 1997).…”
Section: Colour Deconstructionmentioning
confidence: 99%